Challenging American Leadership Impact of National Quality on Risk of Losing Leadership - Frankel, E.G (Topics in Safety, Risk, Reliability and Quality, 2006)
After leading the world during most of the 20th century in economic, political, technological, military, and even social terms, America's role is now being challenged. Its values questioned, and its methods often disparaged, America had become the clear example to be followed or even copied, yet its more recent strategic and political decisions gained little international support and a lot of outright opposition. The quality of its national planning and decision making has been severely compromised, and risk management appears to be largely absent. India and China are now emerging as new economic powers, with advancing technological prowess. Their focus is on socioeconomic development, but their capabilities and potentials are much broader and may challenge America's leadership before long, unless it recognizes the changing demands of the new wide open globalized world.